Rice videos, with a similar initiative: IITA video viewing club - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
WARDA’s rice videos are available in more than 20 African languages, and are seen on national television in Gambia, Guinea, Nigeria and Uganda. The videos explain the 'how to’s' and the 'why’s' behind the technologies and processes. They were based on adult-learning  principles, fully valorizing and building on farmers’ knowledge.